Applications of stochastic models in the storage dams sizing - Horqque Ferro, Saúl (2011)
The techniques for generating synthetic samples provided by stochastic hydrology have proved to be a powerful tool for advanced application of stochastic processes in hydrology and treatment of problems related to the size of the storage dams, mainly in areas with limited information hydrological as well as the planning and operation of water resource utilization. Indeed, stochastic hydrology allows the generation synthetic hydrologic series based on the analysis of the structure of short records, thus providing a panorama of possibilities of occurrence with hydro availability in the future, which allows a degree reliability than traditional methods, determining the main dimensions of the dam. This paper presents a methodology to show the synthetic data generation based on existing historical samples and with them running a simulation of the vessel to determine appropriate levels of operation while the optimum height of the dam considering the required demand and the availability of hydropower.